2020
DOI: 10.3389/fpsyg.2020.579205
|View full text |Cite
|
Sign up to set email alerts
|

The Big Three Health Behaviors and Mental Health and Well-Being Among Young Adults: A Cross-Sectional Investigation of Sleep, Exercise, and Diet

Abstract: BackgroundSleep, physical activity, and diet have been associated with mental health and well-being individually in young adults. However, which of these “big three” health behaviors most strongly predicts mental health and well-being, and their higher-order relationships in predictive models, is less known. This study investigated the differential and higher-order associations between sleep, physical activity, and dietary factors as predictors of mental health and well-being in young adults.MethodIn a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 55 publications
2
42
0
1
Order By: Relevance
“…It is possible that our results are due to insuffi-cient consideration of the exact amount of FV servings per day; it has been stated that FV consumption and SWB indicators have a linear dose-response relationship [19,20,60,64,65] and that optimal intake is ≥7-8 servings per day [19,20,26], something that has also been postulated for physical and mental health outcomes [66], although others have indicated that minimal increments in consumption not reaching the "5 a day" recommendation are also associated with substantial increases in happiness [60,64], overall health, and quality of life [67]. Another possible explanation is that it has been demonstrated that raw compared to prepared FV is more associated with increments in SWB [24,27]. Future research is needed to reach more consistent findings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that our results are due to insuffi-cient consideration of the exact amount of FV servings per day; it has been stated that FV consumption and SWB indicators have a linear dose-response relationship [19,20,60,64,65] and that optimal intake is ≥7-8 servings per day [19,20,26], something that has also been postulated for physical and mental health outcomes [66], although others have indicated that minimal increments in consumption not reaching the "5 a day" recommendation are also associated with substantial increases in happiness [60,64], overall health, and quality of life [67]. Another possible explanation is that it has been demonstrated that raw compared to prepared FV is more associated with increments in SWB [24,27]. Future research is needed to reach more consistent findings.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have included individuals with overweight and obesity in their samples (e.g., [21][22][23]), but have not analyzed possible differences. A few studies aiming to explore the influence of BMI or weight status did not support an influence for positive indicators of well-being, and contradictory findings were obtained for negative indicators; however, these studies were conducted with young adults in the normal range of weight status (e.g., [24][25][26][27]). In contrast, some findings with populationbased samples (e.g., [23]) tend to support the same pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The rst predictor selected into the submodel was sleep quality -how refreshed participants felt after waking up, on their average day. Sleep quality has been consistently shown to be one of the strongest predictors of well-being, especially in young adults, with poor sleep quality being strongly linked to poor mental health outcomes including symptoms of depression (Pilcher et al, 1997;Ridner et al, 2016;Wallace et al, 2017;S.-R. Wickham et al, 2020;Wilson et al, 2014). Additionally, while sleep quality has often been shown to be an important predictor of well-being, sleep quantity has not (Pilcher et al, 1997;Wallace et al, 2017), and this is congruent with our results -while sleep quality was entered into the submodels early along the feature selection trajectory, sleep quantity was only entered long after any improvement in predictive accuracy was shown, indicating a lack of predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the 1 SE rule, fruit consumption only was su cient to approximate the reference model's predictions, suggesting that fruit consumption may contain enough information about the quality of one's diet to make other diet-related predictors redundant. Additionally, there is evidence that raw fruit and vegetables are stronger predictors of well-being than cooked fruit and vegetables (Brookie et al, 2018;S.-R. Wickham et al, 2020), and since fruit is more often eaten raw, general fruit consumption may be a stronger indicator of good diet than vegetable consumption. Be it as it may, sleep quality, having trouble concentrating, and fruit consumption are all meaningful predictors within the well-being literature.…”
Section: Discussionmentioning
confidence: 99%
“…PA has been shown to be associated with depression among university students [ 7 , 9 , 10 , 11 , 12 , 13 , 14 ]. Some evidence suggests that high levels of PA can play a protective role as a counter to the negative effects of SB on all causes of mortality [ 15 ], and on self-reported mental and social health outcomes in some regions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%